Overview of EEG Research in Early Childhood Education: An International Perspective (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2018)
The aim of this article is to provide an understanding related to the basics of data collection with electroencephalogram (EEG) technology in the field of early childhood education. With today’s rise in lab research with EEG, the commercially available portable EEG machines are being used more readily. With them it is becoming cheaper and easier to conduct research and collect EEG recordings. A review of the literature allows for comparison between research grade EEG technology and portable EEG technology, revealing the validity of portable EEG research. The advantages and disadvantages of portable EEGs vs research grade EEG is reviewed in light of research with the population of young learners.